Custom CARs: Leveraging the Adaptability of Allogeneic CAR Therapies to Address Current Challenges in Relapsed/Refractory DLBCL - Jeyakumar, Nikeshan; Smith, Melody (Frontiers in Immunology, 2022)
Cellular therapies have transformed the treatment of relapsed/refractory diffuse large B-cell lymphoma (r/r DLBCL), which typically does not respond well to salvage chemotherapy. Recently, approximately 40% of r/r DLBCL patients across three different trials achieved a complete remission at 1 year after receiving treatment with autologous chimeric antigen receptor (CAR) T cells (auto-CARs). These successes have prompted studies of auto-CARs in second-line settings, in which axicabtagene ciloleucel and lisocabtagene maraleucel both showed improved event-free survival over autologous hematopoietic cell transplantation (AHCT). While encouraging, this data also highlights that 60% of patients relapse or progress following treatment with auto-CARs. Individual disease characteristics and logistical challenges of cell engineering also limit patients’ eligibility for auto-CARs. Allogeneic CAR T cells (allo-CARs) may address some of these limitations as they may mitigate delays associated with auto-CARs, thereby reducing the need for bridging chemotherapies and increasing availability of cellular products for patients with aggressive lymphomas. By being sourced from healthy donors who have never been exposed to cytotoxic chemotherapy, allo-CARs can be created from T cells with better fitness. Allo-CARs made from specific cellular subsets (e.g., stem cell memory or naïve/early memory T cells) may also have increased efficacy and long-term persistence. Additionally, allo-CARs have been successfully created from other cell types, including natural killer cells, gamma-delta T-cells and induced pluripotent stem cells. These cell types can be engineered to target viral antigens, enabling precision targeting of virally driven DLBCL. As allogeneic donor cells can be banked and cryopreserved in batches, they can be made more readily available, potentially reducing logistical hurdles and costs compared to engineering auto-CARs. This may ultimately create a more sustainable platform for cell therapies. Challenges with allo-CARs that will need to be addressed include graft versus host disease, alloimmunization, potentially decreased persistence relative to auto-CARs, and antigen escape. In short, the adaptability of allo-CARs makes them ideal for treating patients with r/r DLBCL who have progressed through standard chemotherapy, AHCT, or auto-CARs. Here, we review the published literature on patients with r/r DLBCL treated with allogeneic CAR products manufactured from various cell types as well as forthcoming allogeneic CAR technologies.